Density Functional Theoretical Computational Studies on 3-Methyl 2-Vinyl Pyridinium Phosphate - N. Kanagathara; V. J. Thanigaiarasu; V. Sabari; S. Elangovan (Advances in Condensed Matter Physics)
The molecular structure of 3-methyl 2-vinyl pyridinium phosphate (3M2VPP) has been optimized by using Density Functional Theory using B3LYP hybrid functional with 6-311++G (d, p) basis set in order to find the whole characteristics of the molecular complex. The theoretical structural parameters such as bond length, bond angle, and dihedral angle are determined by DFT methods and are well agreed with the single crystal X-ray diffraction parameters. Theoretical vibrational, highest occupied molecular orbital - lowest unoccupied molecular orbital (HOMO-LUMO), natural bonding orbital (NBO), and electrostatic potential (ESP) analyses have also been performed. Based on the potential energy distribution (PED), the complete vibrational assignments, analysis, and correlation of the compound’s fundamental modes have been determined. Natural bonding orbital (NBO) analysis is used to evaluate the intramolecular charge transfer and hyper-conjugative interaction of the molecule. B3LYP/6-311++G (d, p) basis set determines the electronic properties such as HOMO–LUMO energies and is used to understand the kinetic stability and chemical reactivity of the studied compound. Molecular electrostatic potential (MEP) is used to investigate the electron density distribution and chemical reactive sites of 3M2VPP. The dipole moment, total polarizability, and the first-order hyperpolarizability calculations have been carried out for the studied molecule. Hirshfeld surface analysis has been done to study the intermolecular interactions in the studied complex.